2019
DOI: 10.1038/s41598-019-45494-4
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic Characterization of Emerging Avian Reovirus Genetic Variants in California

Abstract: This study focuses on virus isolation of avian reoviruses from a tenosynovitis outbreak between September 2015 and June 2018, the molecular characterization of selected isolates based on partial S1 gene sequences, and the full genome characterization of seven isolates. A total of 265 reoviruses were detected and isolated, 83.3% from tendons and joints, 12.3% from the heart and 3.7% from intestines. Eighty five out of the 150 (56.6%) selected viruses for sequencing and characterization were successfully detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
41
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 24 publications
3
41
0
1
Order By: Relevance
“…Based on the σC protein sequence, the phylogenetic analysis revealed that our isolates from wild birds belonged to GC I, which is the predominant cluster in chicken-origin ARVs ( 28 ). This includes commercial vaccine isolates and induces the production of the disease in chickens by experimental infection ( 8 , 40 ). Genetic similarities of ARVs from wild birds and poultry support the hypothesis of circulation of ARVs between wild birds and poultry.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the σC protein sequence, the phylogenetic analysis revealed that our isolates from wild birds belonged to GC I, which is the predominant cluster in chicken-origin ARVs ( 28 ). This includes commercial vaccine isolates and induces the production of the disease in chickens by experimental infection ( 8 , 40 ). Genetic similarities of ARVs from wild birds and poultry support the hypothesis of circulation of ARVs between wild birds and poultry.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously applied SISPA strategy for whole genome sequencing of avian single strain RNA viruses, including avian influenza virus, Coronavirus and Paramyxovirus [26]. In 2012, there were a few reports that regards to a newly emerging reovirus in USA and China in avian species [15,17,27].…”
Section: Discussionmentioning
confidence: 99%
“…Avian Orthoreoviruses (ARVs) have been isolated from enteric disease syndromes, myocarditis, hepatitis, arthritis/tenosynovitis, malabsorbstion syndrome in commercial poultry and are responsible for economic loss in poultry worldwide [12][13][14]. Recently, newly emerging avian reovirus variants were isolated in the USA [15][16][17] or China [18]. The molecular characterization of avian reoviruses is based on amplification of the amino acid sequence of the Sigma C. Sigma C is a major antigenic determinant of ARVs and the most genetically variable gene within the reovirus genome [16,[19][20][21].…”
mentioning
confidence: 99%
“…We classified reovirus isolates in this study based on the σC protein, all isolates belonged to genotypic cluster I, which is the predominant cluster in chicken-origin ARVs and includes commercial vaccine isolates (Figure 3) (8,53). Similar results in wild birds were described in the UK and ARV isolated from free-living magpie (Pica pica) belonged to genotypic cluster I (31).…”
Section: Discussionmentioning
confidence: 66%
“…For the σNS protein, deduced amino acid substitutions at positions 72, 121, 152, 158, 160, 162, 218, 254, 273, and 350 were observed for all isolates with respect to S1133 (Table 3). These substitutions were also observed for the Californian chicken-origin isolate K1600657 that was associated with severe clinical signs (53). These findings suggested that pathotyping based on the σC protein has limitations.…”
Section: Discussionmentioning
confidence: 79%